"How intense is this silence?" A multiple method study investigating music therapy for young children with selective mutism. Issue 1 (1st June 2016) - Jones, Kate
Abstract : Background : Selective mutism (SM) is a debilitating anxiety disorder that can affect children when they begin school or nursery. The usual presentation is a persistent lack of speech in the education setting, contrasting with confident speech at home. The long-term impact of the disorder, if untreated, can be severe. There is some evidence to suggest music therapy is helpful but clearer understanding of the therapeutic process is needed. Methods : Literature reviews, survey and interviews with music therapists, and multiple case studies of music therapy for young children with SM were used to evaluate and refine a theoretical framework describing music therapy as an intervention for SM. A heuristic approach was used to analyse and synthesise data. Results : Preliminary analysis across datasets supports and enriches key aspects of the framework. Playful improvisation, oral instruments and the opportunity to make loud sounds emerge as key features of the music therapy process. Discussion : Initial findings suggest a positive contribution for music therapy as part of a multi-modal approach to the treatment of SM in young children, and will inform the development of clinical guidelines.